Deposition of silica in hydrometallurgical processes - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Introduction/purpose: Dissolution of nonferrous metals from oxidic ores such as laterite, high silicon bauxite and eudialyte during acidic treatment was connected with silica gel formation. Methods: Familiarity with behavior of silica in hydrometallugical processes such as dissolution at atmospheric and high pressure, precipitation, neutralization and filtration is most important for the recovery of metals from water solution. Results:. Gel formation was avoided using dry digestion and a carbonation process of olivine under high pressure in an autoclave. Conclusion: Fine silica was prepared from olivine in water solution at 175°C and 120 bar for 4 hours in an autoclave using some additives such as sodium bicarbonate and oxalic acid.